Assessing the Viability of Growing Agave Tequilana as a Biofuel Feedstock in Queensland, Australia - Subedi, Roshan; Akbar, Delwar; Ashwath, Nanjappa; Rolfe, John; Rahman, Azad (International Journal of Energy Economics and Policy, 2017)
This study assessed farmer’s perceptions about cultivating Agave tequilana for bio-ethanol production in Australia and its economic viability. This plant has been growing in Ayr, a trial site in Queensland, Australia. This study found both farmers and stakeholders are ready to accept Agave tequilana as a potential biofuel crop because farmers can use their marginalised land, where they require less water and nutrients. Commercial farming of Agave tequilana could be supported in Queensland by existing sugar mills, infrastructure and technologies to minimise the cost associated with transport and processing. An economic model has been developed with a sensitivity analysis to assess the net present value of bioethanol production over a 40 year period. Keywords: Agave tequilana, bioethanol production, Ayr, Queensland JEL Classifications: Q42, Q48, R14